Development of Learning Media About Healthy Life Culture for Second Grade Students of Elementary School - Pradipta, Riyanda Pandu; Rahayu, Tandiyo; Hidayah, Taufiq (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
Physical education's learning especially healthy cultural life material constrained by the lack of teaching materials in the form of learning books and also the unavailability of interactive learning media. Therefore, researchers interested in developing textbooks and interactive learning media of healthy living culture material that is able to attract and stimulate student creativity. From textbooks and interactive learning media is expected to become a source of learning and new learning media that can reduce the static atmosphere so as to create an interesting and enjoyable learning process. The results of this study are assessments of the students of large-scale pemasorkes are: (1) quality aspects of instructional media, (2) aspects of media application in the field, (3) aspect of interest in the product. Student appraisal shows that the medium of learning about healthy living culture has a